HUBUNGAN RELIGIUSITAS DENGAN SELF-REGULATED BEHAVIOR SANTRI PONDOK PESANTREN DARUL IKHLAS PAKANDANGAN - Nur Alim; M. Hubbal Khair; Nurva Dillatul Vatin; Lusi Tania Agustin (Affection: Journal of Psychology And Counseling, 2025)
This research is motivated by the phenomenon that occurs regarding the behavior of students (santri) who live and study at Islamic boarding schools (pesantren). Although they come from an Islamic educational background, many of them do not behave as expected, while others demonstrate normal behavior in accordance with their educational background. One of the factors influencing behavior is religiosity and self-regulated behavior. The purpose of this study is to determine the relationship between religiosity and self-regulated behavior among students of Pondok Pesantren Darul Ikhlas Pakandangan. This study employs a quantitative method with data analysis techniques using linear regression analysis, processed with SPSS version 20.0 for Windows. The population in this research consists of 100 students of Pondok Pesantren Darul Ikhlas Pakandangan, with a total sample size of 100 students, selected using probability sampling techniques. The data collection technique used in this study is a psychological scale based on the Likert model. Two scales were used as measurement instruments: a modified religiosity scale consisting of 31 valid items with a reliability coefficient of 0.892, and a self-regulated behavior scale developed by the researcher consisting of 44 valid items with a reliability coefficient of 0.893. Based on the results of data analysis, the simple linear regression test shows that the t-value is greater than the t-table (6.905 > 1.668), which means the hypothesis is accepted. In other words, religiosity has an effect on students’ self-regulated behavior. The positive t-value indicates that the effect is positive, and the significance value of 0.000 is less than 0.05, meaning the hypothesis is accepted. Thus, it can be concluded that religiosity is positively related to self-regulated behavior among the students of Pondok Pesantren Darul Ikhlas Pakandangan.